The situation of field training programme and its role in giving female students the necessary skills to practise the profession of an educator (A field study from the viewpoint of fourth year female students in the department of kindergartens) - Ahmad , Mutieah; Zmourod , Amira (Latakia University Journal - Arts and Humanities Sciences Series, 2016)
The study aimed to get acquainted with the situation of field training in the department of kindergartens in the faculty of Education at Tishreen University, and this training role in giving female students the necessary skills to practice the career of an educator from the view point of fourth year female students. The two researchers followed the descriptive approach. The subject of the study, which is a questionnaire, was distributed to a random sample consisting of seventy female students form November 1st to December 15th, 2014.Mathematical medians and relative weights were used to analyse data. The study got to know the most important points of strength and weakness in the field training programme. The study also showed the students, appreciation of the programme’s ability to give them the necessary skills to be educators in the future. It also showed a medium degree of satisfaction with the programme in general. The study recommended an increase in field training hours as well as an increase in the number of kindergartens where female students can train so that they can apply theoretical knowledge more practically.